Effect of Organizational Support on Police Effectiveness and Behavior: a Cross-cultural Comparison - Boateng, Francis D. (Asian journal of criminology, 2018)
Organizational support has received considerable attention in the academic literature. However, in policing, this area of research has received limited attention. The present study surveyed police officers from two countries to investigate how officers’ perception of organizational support influence their sense of effectiveness and behavior. Findings revealed significant cultural differences in the perception of organizational support and its impact on perceived effectiveness and behavior in the two countries. Policy implications of the findings are discussed.